Chi phí điều trị trực tiếp do biến chứng huyết khối tĩnh mạch 90 ngày sau phẫu thuật - Bùi, Mỹ Hạnh (H. : ĐHQGHN, 2020)
Study object: Describe the direct treatment costs due to venous thromboembolism complications 90 days after surgery by using national health insurance reimbursement database. Patients: 824,947 adult patients who underwent major surgeries were enrolled from January 1, 2017 to September 31, 2018. Method: Study was conducted by using cross-sectional descriptive design. Patients were considered VTE case if they had a diagnostic code up to 90 days after the first surgery, thus 1472 were diagnosed as having VTE after surgery. The study using propensity score matching method shows that there were 913 pairs of patients with the same propensity score included in analysis. Results: The rate of hospital re-admission and outpatient visit were 41.7% and 60.8% in group of VTE patient after matching, respectively. The mean 90-day postoperative cost in VTE group after matching was found to be 89.652 ± 107.928 thousand VNĐ, which is 1.5 times higher than the expenditure of non-VTE group with 61.474± 81.115 thousand VNĐ. Conclusion: The costs related to VTE treatment can be used to evaluate the potential economic benefit and cost-savings from efforts of VTE prevention.